Physical examination of the spine - Albert, Todd J.; Vaccaro, Alexander R. (Thieme Medical Publishers, 2005)
This concise source for the clinical anatomy of the visual system covers the clinical anatomy of the eye, its adnexa and the visual pathways in a well illustrated well referenced format. It balances histologic content of the microscope anatomy with functional aspects of the eye and visual system.